Integrity of Financial Statements: An Empirical Study in Indonesia - Suzan, Leny; Iqbal, Muhammad (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2024)
The integrity of financial reporting depends on the accuracy and objectivity of the data given. Another technique to assess a company's reliability in providing financial data is by looking at their reporting integrity. The purpose of this study is to investigate the relationship between intellectual capital, leverage, and the credibility of financial statements from an institutional ownership perspective. The following transportation and logistics businesses were chosen using a purposive sample technique: all companies listed on the Indonesia Stock Exchange from 2018 to 2022. The researchmethodology for this study is panel data regression, and Eviews 12 will be used for data analysis. The study's findings indicate that all three independent factors have an impact on financial report integrity concurrently; Intellectual capital has no effect, Leverage has a negative impact, and institutional ownership positive effect.